2018
DOI: 10.1093/eurheartj/ehy182
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of statin therapy: perception vs. the evidence – focus on glucose homeostasis, cognitive, renal and hepatic function, haemorrhagic stroke and cataract

Abstract: AimsTo objectively appraise evidence for possible adverse effects of long-term statin therapy on glucose homeostasis, cognitive, renal and hepatic function, and risk for haemorrhagic stroke or cataract.Methods and resultsA literature search covering 2000–2017 was performed. The Panel critically appraised the data and agreed by consensus on the categorization of reported adverse effects. Randomized controlled trials (RCTs) and genetic studies show that statin therapy is associated with a modest increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
185
1
29

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(244 citation statements)
references
References 138 publications
2
185
1
29
Order By: Relevance
“…20,21 This tubular toxicity has been reported in rare case reports, 22 sometimes associated with tubulointerstitial nephritis. 23 Nevertheless, randomized trials have shown that statins may also have renoprotective effects, 24 especially in diabetic patients, 25 even when prescribed at high doses, or when given for prevention of contrast-induced AKI. 26,27 Of note, a metaanalysis showed similar renoprotective effects in high CVD risk patients treated with atorvastatin and rosuvastatin prescribed at commonly used doses.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 This tubular toxicity has been reported in rare case reports, 22 sometimes associated with tubulointerstitial nephritis. 23 Nevertheless, randomized trials have shown that statins may also have renoprotective effects, 24 especially in diabetic patients, 25 even when prescribed at high doses, or when given for prevention of contrast-induced AKI. 26,27 Of note, a metaanalysis showed similar renoprotective effects in high CVD risk patients treated with atorvastatin and rosuvastatin prescribed at commonly used doses.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects were rare in large double-blind placebocontrolled trials. 14 Given the investigation results, we would favour statin use. This is in accordance with most guidelines and should be in the context of shared decision-making with the patient.…”
Section: What Other Patient Factors Should Be Considered?mentioning
confidence: 99%
“…Adequately addressing the benefits and risks of statins may improve adherence. Side effects were rare in large double‐blind placebo‐controlled trials . It may be worthwhile gauging the patient's understanding and perceived risk.…”
Section: What Other Patient Factors Should Be Considered?mentioning
confidence: 99%
“…These six stains are associated with mildly to moderately elevated transaminase levels, and according to a large-scale study conducted in Europe and the US, in many cases they appear in 0.5% to 2.0% of cases within the first three months of administration. Systematic meta-analyses of 135 RCTs that included a total of 246,000 patients reported that statins have approximately 50% higher risk of elevated transaminase levels than controls and placebos, and that in the cases of Atorvastatin, Rosuvastatin, and Simvastatin, the enzyme elevations are dose-dependent [39][40][41] . However, the overall frequency of 0.5% to 2.0% was nearly the same as that for the placebo.…”
Section: Liver Injurymentioning
confidence: 99%